Down-regulation of miR-23b induces phenotypic switching of vascular smooth muscle cells in vitro and in vivo. (20th May 2015) - Iaconetti, Claudio; De Rosa, Salvatore; Polimeni, Alberto; Sorrentino, Sabato; Gareri, Clarice; Carino, Annarita; Sabatino, Jolanda; Colangelo, Maria; Curcio, Antonio; Indolfi, Ciro
Abstract: Aims: Phenotypic switch of vascular smooth muscle cells (VSMCs) plays a key role in the pathogenesis of different vascular diseases, such as atherosclerosis and restenosis after coronary intervention. MicroRNAs have been identified as key regulators of VSMC biology. The miR-23b is highly expressed in VSMCs and it is involved in differentation, proliferation, and migration of several non-vascular cell types. However, the role of miR-23b in vascular disease is currently unknown. Thus, the aim of the present study was to evaluate the role of miR-23b on VSMC phenotypic switch in vitro and after vascular injury in vivo . Methods and results: To determine the changes of miR-23b expression in the injured arterial wall, we used the standard rat carotid artery balloon injury model. In vivo studies demonstrated that miR-23b is down-regulated after vascular injury. Gain-of-function studies showed that overexpression of miR-23b inhibited VSMC proliferation and migration, whereas the opposite effect was obtained with the in vitro inhibition of miR-23b. We further demonstrated that miR-23b can significantly promote the expression of VSMC marker genes such as smooth muscle α-actin (ACTA2) and smooth muscle myosin heavy chain (MYH11). Overexpression of miR-23b in balloon-injured arteries by Ad-miR-23b markedly decreased neointimal hyperplasia. Finally, miR-23b specifically suppresses urokinase-type plasminogen activator, SMAD family member 3, and transcription factor forkhead box O4 (FoxO4) expression in phenotypically modulated VSMCs. By luciferase reporter assay, we validated the transcription factor FoxO4 as a direct target of miR-23b in VSMCs. Conclusions: We identify miR-23b as a novel regulator of VSMC phenotypic switch in vitro and following vascular injury in vivo .